Dr. Axelrod's mini-atlas of freshwater aquarium fishes - Axelrod, Herbert R. (Neptune City, N.J. : T.F.H. Publications, 1987)
Color photos and text identify aquarium fishes. Also includes selection, care, and breeding section featuring aquarium plants.
Includes index.
Keywords: Peces de agua dulce; Peces de acuario; Aquarium fishes -- Identification; Acuarios